Bioactive Compounds from Basil (Ocimumbasilicum) Essential Oils with Larvicidal Activity against Aedesaegypti Larvae - Azhari, H. Nour; Nour, A. H.; M. M., Yusoff; Jessinta, D/O Sandanasamy (2012)
Abstract. Dengue, yellow fever and dengue haemorrhagic fever are health problems in many countries. The Aedesaegypti mosquito is the major vector for these diseases. The development of insect resistance and side effects associated with synthetic pesticides make essential oils the focus of intense research efforts because of their biological activities and long, safe use as natural products. In this study, the essential oils from two basil (O. basilicum) accessions were tested in a laboratory bioassay for larvicidal activity against third instar A. aegypti larvae. The essential oils were extracted by steam distillation, and their chemical compositions were determined by GC-MS. Approximately 13 compounds (>1%) were detected; most compounds were oxygenated monoterpenes. Methyl chavicol and geranial were the predominant compounds in the two observed accessions. For the bioassay, six concentrations (50, 100, 200, 300, 400 and 500 µg/ml) of essential oil solutions were prepared from the two basil accessions. For each concentration of oil solution, 25 third instar larvae were inserted. Controls, 1% DMSO or untreated larvae in tap water were also performed for comparison. The active ingredients in the essential oils were separated and identified by TLC and GC-MS. The larval assays provided LC50 and LC90 values for the methyl chavicol accession (MCV) were 160 and 262µg/ml, respectively; the values for the geranial-geraniol accession (GGV) were 174 and 356µg/ml, respectively. Linalool, geraniol, geranial, methyl chavicol and eugenol were active components against A. aegypti larvae.